GE_GERICHTE A/261/2025 vom 29. Januar 2025 - GE Cour de justice (2025)
MESURE DE CONTRAINTE(DROIT DES ÉTRANGERS);DÉTENTION AUX FINS D'EXPULSION;PROCÉDURE ÉCRITE | LEI.80.al3; LEI.76.al1.letb.ch1; LEI.75.al1.chc; LEI.75.al1.chh